2017
DOI: 10.1093/aesa/saw064
|View full text |Cite
|
Sign up to set email alerts
|

Bumble Bees (Hymenoptera: Apidae) of Montana

Abstract: Montana supports a diverse assemblage of bumble bees (Bombus Latreille) due to its size, landscape diversity, and location at the junction of known geographic ranges of North American species. We compiled the first inventory of Bombus species in Montana, using records from 25 natural history collections and labs engaged in bee research, collected over the past 125 years, as well as specimens collected specifically for this project during the summer of 2015. Over 12,000 records are included, with 28 species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 34 publications
(51 reference statements)
2
32
0
Order By: Relevance
“…The longitudinal range of the species is primarily bound by the crest of the Sierra Nevada and Cascade Mountains in the west, and the Black Hills of South Dakota in the east (Figure ). Although populations of B. huntii have been found east of the montane environment of South Dakota, they have been documented in low abundance relative to surveys of bumble bee communities in Nevada, Utah, Colorado, Montana (Dolan et al., ; Koch et al., ). Finally, B. huntii and its sibling species B. vosnesenskii diverged from their most recent common ancestor by the early Pliocene (~5 mya) (Cameron, Hines, & Williams, ; Hines, ).…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal range of the species is primarily bound by the crest of the Sierra Nevada and Cascade Mountains in the west, and the Black Hills of South Dakota in the east (Figure ). Although populations of B. huntii have been found east of the montane environment of South Dakota, they have been documented in low abundance relative to surveys of bumble bee communities in Nevada, Utah, Colorado, Montana (Dolan et al., ; Koch et al., ). Finally, B. huntii and its sibling species B. vosnesenskii diverged from their most recent common ancestor by the early Pliocene (~5 mya) (Cameron, Hines, & Williams, ; Hines, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Dolan et al (2017) reported a specimen of Bombus borealis Kirby from this study to be a first Montana state record. In effect, this brings the number of known bee species in Montana up from 366 (Kuhlman and Burrows 2017) to at least 372, and indicates a clear need for more extensive bee surveys in the state.…”
Section: Discussionmentioning
confidence: 74%
“…Because Montana spans a large area of diverse topography, landscape and climate (Dolan et al 2017), species groups are likely to vary among different locations. For instance, compared with a checklist of bees from a similar montane habitat in Montana (Kuhlman and Burrows 2017), there was some overlap among species, with 121 species (not including morphospecies) in common with our list, but also some variability, with 126 species unique to our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Montana’s bee fauna is one of the least-studied amongst US states (but see Kuhlman and Burrows 2017, Dolan et al 2017, Reese et al 2018); of the few studies that have been conducted in Montana, even fewer have examined wild bees in agricultural systems. Documenting the diversity of bees on farmlands is important for identifying potential crop pollinators, for gauging the potential of farmland habitats to support overall bee diversity on and around farms and for guiding bee conservation measures (Burkle et al 2017).…”
Section: Introductionmentioning
confidence: 99%